2019
DOI: 10.3390/cancers11020203
|View full text |Cite
|
Sign up to set email alerts
|

Utility of FIB4-T as a Prognostic Factor for Hepatocellular Carcinoma

Abstract: Background: Most integrated scores for predicting the prognosis of patients with hepatocellular carcinoma (HCC) comprise tumor progression factors and liver function variables. The FIB4 index is an indicator of hepatic fibrosis calculated on the basis of age, aspartate aminotransferase (AST) levels, alanine aminotransferase (ALT) levels, and platelet count, but it does not include variables directly related to liver function. We propose a new staging system, referred to as “FIB4-T,” comprising the FIB4 index a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…), liver fibrosis markers (e.g., FIB4 index > 3. 25), and/or laboratory data (e.g., lower platelet count or prolonged prothrombin time) [26][27][28][29][30].…”
Section: Patientsmentioning
confidence: 99%
“…), liver fibrosis markers (e.g., FIB4 index > 3. 25), and/or laboratory data (e.g., lower platelet count or prolonged prothrombin time) [26][27][28][29][30].…”
Section: Patientsmentioning
confidence: 99%
“…A previous study reported that there are three distinct TME phenotypes in HCC that are prominently associated with prognosis, immune surveillance, immune escape, and genetic alterations ( Liu et al, 2021e ). Liver fibrosis indicates tremendous potential in tumorigenesis and tightly correlates with prognosis ( Kariyama et al, 2019 ). Inflammation bursts and the immune responses activate hepatic stellate cells (HSCs) and favor extracellular matrix (ECM) deposition, leading to liver fibrosis ( Koyama and Brenner, 2017 ; Mack, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The FIB‐4 score was used to define the risk of advanced fibrosis as follows: <1.30 (“low risk”), 1.30–2.67 (“intermediate risk”), and ≥2.67 (“high‐risk”) 33 . Additionally, based on previous research findings of enhanced HCC diagnostic performance with increasing FIB‐4 scores, we conducted an investigation to assess the results based on varying FIB‐4 score cutoff values 34–37 …”
Section: Methodsmentioning
confidence: 99%
“…33 Additionally, based on previous research findings of enhanced HCC diagnostic performance with increasing FIB-4 scores, we conducted an investigation to assess the results based on varying FIB-4 score cutoff values. [34][35][36][37]…”
Section: Measurementsmentioning
confidence: 99%